Mission: Impossible. Rogue nation [videorecording (DVD)] - McQuarrie, Christopher; Cruise, Tom, 1962-; Ferguson, Rebecca, 1983-; Renner, Jeremy; Rhames, Ving, 1961-; Baldwin, Alec, 1958- (Paramount Pictures, 2015)
With their elite organization shut down by the CIA, agent Ethan Hunt and his team must race against time to stop The Syndicate, a deadly network of rogue operatives turned traitors. To stop this global threat, Ethan must join forces with an elusive, disavowed agent whose loyalty is suspect as he faces his most impossible mission ever.